ENERGY-EFFICIENT WINDOW RESTORATION: INNOVATIVE APPROACHES TO HEAT CONSERVATION IN HISTORIC BUILDINGS - Klykailo, Vitalii (European Journal of Interdisciplinary Issues, 2025)
The restoration of historic buildings aims to preserve and maintain the durability of structures, improve their energy efficiency, and create a safe indoor climate. The purpose of this article is to analyze modern approaches and technologies for window restoration in the context of historic building restoration, which allow for reduced heat loss without compromising architectural authenticity. Based on the study of historical and modern experience in the preservation of architectural monuments, the study formulates key architectural and engineering solutions that ensure the preservation and durability of monuments of historically valuable architecture. The article discusses the topic of window replacement, which is relevant for reconstructed historic buildings. In particular, it is proposed to replace traditional wooden windows in the reconstruction of historic buildings with polyvinyl chloride (PVC) windows, subject to approval by the relevant authorities. PVC windows allow you to replicate a wide variety of window shapes and elements, and, if necessary, imitate the most delicate and complex patterns of window frames. At the same time, the tasks of architectural conformity to the original appearance of the building and ensuring modern energy efficiency requirements are solved. It has been proven that an additive approach to reconstruction opens up a range of new opportunities for the practical application of environmentally friendly and recycled materials, which not only minimizes the negative impact on the environment but also integrates the principles of sustainable development. The approaches proposed in the study will reduce heat loss without compromising architectural authenticity and will contribute to the transformation of modern construction concepts in the context of greater environmental friendliness and social responsibility. It is necessary to find solutions that allow preserving the architectural appearance of a historic building and facilitate its energy-efficient operation with minimal costs in each case.